2016
DOI: 10.1177/0261927x16629521
|View full text |Cite
|
Sign up to set email alerts
|

No Space for Others? On the Increase of Students’ Self-Focus When Prodded to Think About Many Others

Abstract: In the present experiment, participants read about the presence of many versus few others in typical student-life situations. They subsequently wrote an essay about their perspectives on learning in groups. Using the program Linguistic Inquiry and Word Count to analyze these essays signified that participants who read prompts that involved many (vs. few) other students used more first-person singular pronouns and fewer words related to others. We interpret this increase in self-focus as a consequence of induce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…Varying information about the virtual presence of others (crowded vs non-crowded) can affect how often learners refer to themselves and others when answering an open question (Hellmann et al, 2016). Therefore, it can be assumed that an individual may not only be affected by crowds in a real social environment but also when having many others in mind, such as by feeling virtually crowded in large online courses like xMOOCs.…”
Section: Dealing With Tasks In a Virtual Crowdmentioning
confidence: 99%
See 1 more Smart Citation
“…Varying information about the virtual presence of others (crowded vs non-crowded) can affect how often learners refer to themselves and others when answering an open question (Hellmann et al, 2016). Therefore, it can be assumed that an individual may not only be affected by crowds in a real social environment but also when having many others in mind, such as by feeling virtually crowded in large online courses like xMOOCs.…”
Section: Dealing With Tasks In a Virtual Crowdmentioning
confidence: 99%
“…When students are aware of the size of an online course, they arguably have the virtual presence of other learners in mind. Furthermore, participating learners may perceive the relevance of their individual participation differently when experiencing virtual crowdedness, which might influence references to oneself and others in response to an open question (see Hellmann et al, 2016). The perception of individual relevance can play an important role for learners’ engagement (see Petty and Cacioppo, 1986), which is also supported by findings of Park and Choi (2009), who showed that experiencing relevance in online courses is an important factor to maintain participation.…”
Section: Dealing With Tasks In a Virtual Crowdmentioning
confidence: 99%
“…For example, Maeng and Tanner (, Study 1) demonstrated that students' cognitive elaborations were lower when they were either in an actual crowded situation or merely asked to imagine being in a pictured crowd (vs. noncrowded) setting. For higher education, Hellmann, Adelt, and Jucks () showed that being given information about the number of others influenced students' written responses on the word level in terms of how many references they made to themselves and to others.…”
Section: Introductionmentioning
confidence: 99%
“…In line with these previous findings, it was predicted that using a conversational (vs. formal) language style in the instructions for an xMOOC scenario would result in better learning outcomes in a transfer task (H1). Drawing on the aforementioned findings reported by Hellmann et al (), it was also assessed whether the wording of high school students' written responses would differ between conditions, that is, whether they would make more references to themselves or to others in a transfer and evaluation task. Therefore, it was predicted that using a conversational language style in an xMOOC scenario would lead to more references to oneself, that is, a higher self‐directedness (H2a).…”
Section: Introductionmentioning
confidence: 99%